2021
DOI: 10.3390/healthcare9050538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Home-Based Pulmonary Rehabilitation Program in Patients with Chronic Obstructive Pulmonary Disease in GOLD B Group: A Pilot Study

Abstract: Patients with chronic obstructive pulmonary disease (COPD) in the Global Initiative for Chronic Obstructive Lung Disease (GOLD) B group can be included in pulmonary rehabilitation (PR) settings outside the hospitals. This study aimed to explore the feasibility of a home-based pulmonary rehabilitation (HBPR) program and assess its impact on patients with COPD in the GOLD B group. A real-world, pre–post intervention study was conducted with 12 weeks of HBPR (presential home visits and phone calls) using the self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…48 These metrics, such as the number of chair raises, are important in evaluating the tolerance of fatigue in patients with COPD and have been associated with symptoms such as dyspnea. 49 Improvements in the 6MWD and other related to exercise-induced fatigue are also seen in other studies that implemented pilates in other pathological conditions. 50,51 Likewise, improving balance in patients with COPD is important because impairments and decline in balance are more pronounced in these patients due to exercise intolerance and dyspnea 52,53 as well as other physiological factors such as muscle weakness 54 and somatosensory deficits.…”
Section: Discussionmentioning
confidence: 56%
“…48 These metrics, such as the number of chair raises, are important in evaluating the tolerance of fatigue in patients with COPD and have been associated with symptoms such as dyspnea. 49 Improvements in the 6MWD and other related to exercise-induced fatigue are also seen in other studies that implemented pilates in other pathological conditions. 50,51 Likewise, improving balance in patients with COPD is important because impairments and decline in balance are more pronounced in these patients due to exercise intolerance and dyspnea 52,53 as well as other physiological factors such as muscle weakness 54 and somatosensory deficits.…”
Section: Discussionmentioning
confidence: 56%
“…The HBPR studies' benefits especially on HADS are proven previously in COPD patients (43)(44)(45). For example, a study by Vilarinho et al demonstrated that some pulmonary parameters plus HADS scores were improved after HBPR in 30 patients with severe COPD (46). Additionally, Wallaert et al studied HBPR in 112 patients with idiopathic pulmonary fibrosis and fibrotic nonspecific interstitial pneumonitis (47).…”
Section: Discussionmentioning
confidence: 97%
“…Cardiopulmonary exercise testing (CPET) is considered the gold standard method used to assess exercise capacity, by providing a measure of the maximum oxygen consumption (VO 2 max), which in turn is the gold standard measure for the assessment of cardiorespiratory fitness (CRF) [4]. Treadmills and cycle ergometers are indicated to assess CRF [1]; however, their use is not always feasible in all settings where rehabilitation programs can be implemented [5], especially in community- [6][7][8] and home-based [9][10][11] programs, because they have high costs and require both specialized instruments and trained personnel [1]. To overcome these limitations, field tests can be more affordable, simple to apply, and better related to patients' demands during activities of daily living [2,12].…”
Section: Introductionmentioning
confidence: 99%